2014
DOI: 10.1017/s0021859614001166
|View full text |Cite
|
Sign up to set email alerts
|

Maize yield response to a phosphorus-solubilizing microbial inoculant in field trials

Abstract: SUMMARYFindings from multi-year, multi-site field trial experiments measuring maize yield response to inoculation with the phosphorus-solubilizing fungus, Penicillium bilaiae Chalabuda are presented. The main objective was to evaluate representative data on crop response to the inoculant across a broad set of different soil, agronomic management and climate conditions. A statistical analysis of crop yield response and its variability was conducted to guide further implementation of a stratified trial and sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 43 publications
3
44
2
Order By: Relevance
“…Yield data from the United States and Argentina were separately analyzed with the GLIMMIX procedure of SAS (Littell et al, 2006;SAS Institute, 2013). The analysis considered the effects of replicates and site (year × location combination) as random, and the effect of the inoculation treatment (IT) as fixed.…”
Section: Discussionmentioning
confidence: 99%
“…Yield data from the United States and Argentina were separately analyzed with the GLIMMIX procedure of SAS (Littell et al, 2006;SAS Institute, 2013). The analysis considered the effects of replicates and site (year × location combination) as random, and the effect of the inoculation treatment (IT) as fixed.…”
Section: Discussionmentioning
confidence: 99%
“…PGPM may have the potential to enhance plant uptake of P from soil [14,18,19]. Improved growth under P-limiting soil conditions as a result of microbial inoculations has been observed in many different plant species, such as mung bean [17], bean [20], maize [21] and wheat [22]. In soil, a large proportion of the total P pool is not directly available for plant uptake [23], and the ability to solubilise phosphates in the rhizosphere has been viewed as an important function of PGPM [24].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi of the genus Penicillium have been shown to have P-solubilising capabilities [31,32], and members of this genus have been observed to have a positive effect on biomass and P uptake of wheat and bean [20]. Wakelin et al [33] found that a strain of P. bilaii is both capable of increasing the yield of medic and lentil in the field and of significantly increasing the level of HCO 3 -extractable P in soil microcosms, and more recently P. bilaii has been found to increase yield in maize in field trials [21]. On the other hand, the positive effect of P. bilaii under P-limited conditions has also been linked in pea to an increase in the root adsorptive capacity under P-limited conditions rather than through increased P solubilisation [34].…”
Section: Introductionmentioning
confidence: 99%
“…As also found for Mn/Zn, there was no beneficial effect of Pen1 and Pen2 at the normal (control) temperature regime and inoculation with Pen1 and Pen2 actually led to a significant reduction in aboveground biomass at 51 DAS of plants grown in the high P soil (Figure ). Several studies have reported beneficial effects of seed inoculation with P. bilaii on plants grown under limited P availability (Asea et al., ; Leggett et al., ). However, in previous work we found that a minimum soil P and nutrient content is needed to ensure the persistence and activity of P. bilaii (Pen1) and to obtain a P. bilaii ‐induced increase in shoot length (Gómez‐Muñoz et al., n.d.), while under low P conditions we observed an increase in root growth due to inoculation with P. bilaii (Gómez‐Muñoz, Pittroff et al., ).…”
Section: Resultsmentioning
confidence: 99%